Green-Themed Project-Based Learning in ELT: Improving EFL Students’ Environmental Sensitivity and Communicative Skills - Jane Elvira Scipio; James Edard Lalira (Journal of Innovative and Creativity, 2025)
The proposed research aims to explore the effectiveness of Green-Themed Project-Based Learning (PBL) in enhancing EFL learners' environmental awareness and communicative capabilities. A quasi-experimental pretest-posttest control group was used, which included 20 university students in a control group with conventional instruction and an experimental group with a green-themed PBL intervention that occurred over four instruction sessions. Two instruments were used in the research: a Likert-type scale of environmental sensitivity and a communicative skills assessment rubric that assesses fluency, vocabulary use, coherence, and interaction. Independent-samples t-tests were also applied to compare gain scores between the groups and to estimate the effect size, which was computed using Cohen’s d. As it was found, students in the experimental group exhibited much higher improvement in both environmental sensitivity (t = -6.52, p < 0.001, d = 1.98) and communicative skills (t = -5.61, p < 0.001, d = 1.71) in comparison with the students in the control group. These findings indicate that Green-Themed PBL is an effective tool that enhances students' ecological awareness and, at the same time, boosts their communicative competence. The study found that implementing environmentally oriented PBL in ELT teaching can offer valuable educational opportunities that help achieve language competency and ecological literacy. The results point to the pedagogical importance of sustainability-oriented learning in EFL classrooms and the tendency to introduce wider application of contextually specific project-based strategies in higher education.